Acute modulatory effects of apple cider vinegar, garlic, ginger, lemon and honey mixture, with and without exercise on postprandial glycemia innon-diabetic females - Ismarulyusda Ishak; Penny George; Farah Wahida Ibrahim; Hanis Mastura Yahya; Nor Farah Fauzi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Postprandial hyperglycemia is independently related to cardiovascular disease. Garlic, ginger, lemon, honey and apple cider vinegar are known to have anti-glycemic properties. However, the effectiveness of combination of these natural products on reducing postprandial glycemia is uncertain. The aim of the present study was to investigate the glucose-lowering effect of a novel mixture consisting of apple cider vinegar, garlic, ginger, lemon, and honey; alone and in combination with exercise in response to a high-carbohydrate meal in non-diabetic individuals. Ten, female subjects (mean age: 25 ± 2.67 years, mean BMI: 22.6 ± 3.5 kg/m2) participated in this randomised, cross-over intervention consisting of four trials: control (CON), mixture only (MIX), exercise only (EX), and exercise + mixture (EX-MIX). All trials involved consumption of a high-carbohydrate breakfast, then followed by rest in CON, consumption of natural product mixture in MIX, brisk-walking exercise in EX, and combination of mixture and exercise in EX-MIX. Blood glucose was measured at fasting, and at 30, 60, 90, 120 minutes post meal. Postprandial glucose response was calculated as area under the glucose curve. Two-way repeated measures ANOVA showed a significant group and time interaction (p < 0.001). Compared to CON, postprandial glucose responses were 8%, 13% and 15% lower in MIX (p = 0.049), EX (p = 0.001) and EX-MIX (p = 0.005) respectively. Postprandial glucose was 8% lower in EX-MIX compared to MIX (p = 0.002). In conclusion, consuming natural product mixture containing garlic, ginger, lemon, honey and apple cider vinegar reduced postprandial glycemia to a certain extent, however, combining mixture with exercise produced a greater attenuation effect compared to consuming mixture alone. This finding is indicative of a potential benefit of the novel mixture as a complementary management of hyperglycemia in high-risk individuals